Inflation Anchoring in the Euro Area - Christian Speck (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Did the decline in inflation rates from 2012 to 2015 and the low levels of market-based inflation expectations lead to de-anchored inflation dynamics in the euro area? This paper is the first time-varying event study to investigate the reaction of inflation-linked swap (ILS) rates - a market-based measure of inflation expectations - to macroeconomic surprises in the euro area. Compared to the pre-crisis period, surprises have a much stronger effect on spot ILS rates during the crisis. Medium-term forward ILS rates remain insensitive to news most of the time, which implies inflation anchoring. Only short periods of sensitivity on the part of medium-term forward ILS rates are identified at times of low inflation or recession. The sensitivity is lower over more distant forecast horizons such that medium-term sensitivity represents an inflation adjustment process and provides no evidence for a de-anchoring of inflation expectations or a loss of credibility for the Eurosystem's policy target.
Keywords: E44; E31; G14; 330